PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK CERITA RAKYAT LAHILOTE BERBASIS BUDAYA LOKAL DI SEKOLAH DASAR - Pobela, Mawarda; Pomalingo, Samsi; Pulukadang, Wiwy Triyanty; Katili, Sukri; Cuga, Candra (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to develop an E-Comic learning media for Lahilote Folklore that meets the criteria for eligibility and effectiveness in supporting Local Content learning, especially in regional folklore material for fourth grade students. The method used is Research and Development (R&D) with a 4D development model, which includes the define, design, develop, and disseminate stages. The feasibility test was carried out through validation by experts. The results of the media validation showed a score of 28, which is included in the "Very Good" category, with a percentage value of 100%. Meanwhile, the material validation obtained a score of 32, which is included in the "Very Good" category with a percentage value of 100%. The practicality of the media was tested using a practitioner validation sheet, which produced a perfect score, which was 44 out of a maximum total score of 44 so that the average percentage of practicality reached 100%, indicating that this media is feasible to use. The average value of all validations reached 100%, indicating that this media is feasible to use in the learning process by elementary school teachers and students. The effectiveness of the media was tested through the results of the student response test in grade IV of SDN No. 76 Kota Tengah. Which gets a percentage of 100% with the category (Very Good) from student responses. Thus, the E-Comic of Lahilote Folk Tales is declared worthy of being distributed.